The Practice of Surgical Pathology A Beginner's Guide to the Diagnostic Process - Molavi, Diana Weedman (Springer International Publishing, 2018)
Within the field of pathology, there is a wide gap in pedagogy between medical school and residency. As a result, the pathology intern often comes into residency unprepared for the practical demands of the field, and without the foundation to digest professional-level textbooks. Completely illustrated in color, this book is uniquely directed at the junior pathology resident, and goes first through some very basic introductory material, then progresses through each organ system. Within each chapter, there is a brief review of salient normal histology, a discussion of typical specimen types, a strategic approach to the specimen, and a discussion of how the multitude of different diagnoses relate to each other. The book's goal is to lay the foundation of practical pathology, and provide a scaffold on which to build more detailed knowledge. The second edition retains the informal voice and brevity of the first edition, but with new and expanded chapters, new illustrations, and updated material.